Deep‐basin macrobenthos of Doubtful Sound, Fiordland, New Zealand - Paul E. Brewin; P. Keith Probert; Mike F. Barker (New Zealand Journal of Marine and Freshwater Research, 2008)
The first quantitative deep‐benthic macrofaunal survey of a New Zealand fjord sampled the macrofaunal communities of 12 deep basins that are spatially subdivided along the two main axes of the Doubtful Sound complex. Within basin communities, there was high between‐sample variability of both abundance and family level alpha diversity. Despite this high variability, basin communities could be separated into high (entrance basins), medium (inner deep basins), and low (inner shallow basins) diversity communities, each having an associated characteristic change in family level beta diversity. Community groupings were comparable to previous qualitative community types described for other fjords in New Zealand. Fiord taxa appeared similar to those found on the continental shelf to the north, although there were some unique elements (Nuculanidae, Neilonellidae, Malletidae, Pronemomeniidae, Trochochaetidae), their presence supporting the notion of “emergent” species in fjord habitats. The observed differences in community composition between basins may represent differences in environmental tolerances or dispersal capabilities.